The effect of glufosinate ammonium in three different textured soil types under Malaysian tropical environment - Tayeb M.A.,; Ismail B.S.,; Mardiana-Jansar K., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Glufosinate ammonium is a broad spectrum, non-selective, contact and organophosphate herbicide which is commonly used in Malaysian oil palm plantations. Research area was one of the oil palm growing areas of Malaysia is located adjacent to the Tasik Chini, Pahang. Farmers use this herbicide to control several types of unwanted plants which could compete with the oil palm for nutrients. Rain water and the sprayed solution are easily adsorbed by soil particles. The glufosinate ammonium sorption was determined by the batch equilibrium technique. The collected soil samples (0-50 cm depth) divided into five groups at 10 cm depth intervals. Glufosinate ammonium adsorption coefficients were correlated with the soil pH, organic matter (OM), clay content, and cation exchange capacity (CEC). Series of glufosinate ammonium standard were as 0.01, 0.1, 0.25, 0.5, 1, 3, 5, and 10 μm/mL. The Linear and Freundlich equations were fitted for obtaining the adsorption and desorption isotherms. The result of the analyses showed that adsorption of glufosinate ammonium was correlated to the clay content. The clay fraction of the soil is the main absorbent of the glufosinate ammonium. Desorption from the soil was indicated by the high binding strength of the adsorbed glufosinate ammonium.